Photosynthesis and Respiration of Baltic Sea Benthic Diatoms to Changing Environmental Conditions and Growth Responses of Selected Species as Affected by an Adjacent Peatland (Hütelmoor) - Prelle, Lara R.; Graiff, Angelika; Gründling-Pfaff, Sigrid; Sommer, Veronika; Kuriyama, Kana; Karsten, Ulf (Frontiers in Microbiology, 2019)
Eight benthic diatom taxa (Actinocyclus octonarius, Melosira moniliformis, Halamphora sp. 1, Halamphora sp. 2, Navicula perminuta, Navicula phyllepta, Nitzschia dubiiformis, Nitzschia pusilla) were isolated from sediments sampled in the southern coastal brackish Baltic Sea and established as unialgal cultures. The coastal shallow water sampling area lies close to a fen peat site (Hütelmoor) and both are connected through an underground peat layer, which might facilitate organic matter and nutrient fluxes along the terrestrial-marine gradient. The photosynthetic performance of these diatoms was measured at different photon fluence rates (0-1200 µmol photons m-2 s-1 at 20 °C) and temperatures (5-40 °C), resulting in light saturation points between 32 and 151 µmol photons m-2 s-1 and maximum net primary production rates of 23 to 144 µmol O2 mg-1 Chl a h-1. None of the species showed severe photoinhibition, and hence all displayed a high photo-physiological plasticity. Photosynthetic oxygen evolution and respirational oxygen consumption between 5 °C and 40 °C revealed eurythermal traits for half of the studied taxa as photosynthetic efficiency was at least 20% of the maximum values at the extreme temperatures. The remaining taxa also indicated eurythermal characteristics, however photosynthetic efficiency of at least 20% was at a narrower temperature range (5 (10) °C to 30 (35) °C). Species-specific optimum temperatures for photosynthesis (15-30 °C) were always lower compared to respiration (25-40 °C). Actinocyclus octonarius and Nitzschia dubiiformis were grown in different defined media, some enriched with Hütelmoor water to test for possible effects of organic components. Hütelmoor water media stimulated growth of both diatom species when kept in a light dark cycle. Actinocyclus octonarius particularly grew in darkness in Hütelmoor water media, pointing to heterotrophic capabilities. The benthic diatoms studied are characterized by high photo-physiological plasticity and a broad temperature tolerance to maintain high primary production rates under wide environmental fluctuations. Organic carbon fluxes from the Hütelmoor into the Baltic Sea may support mixo- and/or heterotrophic growth of microphytobenthic communities. These are essential traits for living in a highly dynamic and variable shallow water environment at the coastal zone of the Baltic Sea.